Cinema brasileiro na estrada: identidade, mitologia e cultura contemporânea no gênero Road Movie (anos 1990-2000) - Gonçalves, Carlos Pereira (2011)
This research has analyzed the social and cultural significance that the road movie narrative genre acquired in the Post-Embrafilme national production (between 1990 and 2000). The core of the research is composed of 11 (eleven) fiction motion pictures produced within this period, among them Central do Brasil, O Caminho das Nuvens, Cinema, aspirina e urubus. The paper has emphasized the understanding on the concept of contemporary culture, its articulations with the symbolic and social imaginary mythology, cultural identity and allegories, assimilated and expressed by the narrative, considering the perspective of the understanding of the historic dimension of the social environment in which this cinema is produced. As to its structuring, the thesis utilizes a theoretical approach of social sciences and, according to concepts, analysis and interpretations that it aims to achieve, it also relies on the areas pertaining to social communication, cinema, literature and music, thus attempting an interdisciplinary approach of study. The central core of the theoretical work is presented in two main streams: Latin American and English Cultural Studies and the Complexity Theory. The results of the research have confirmed the stylistic configuration of the national road movie genre despite its numerical inferiority which was also verified in exploratory research in film production worldwide. The narrative genre which was studied possesses historic mediation with the so called hypermodernity in which the road figure is one of the key elements of symbolic significance: and these are articulate in values, speeches and images with social mobility, individuality, fragmentation and reordering of time and space. A characteristic ontological approach, as well as a remarkable social criticism, was identified in the films studied. The analysis also asserts the relevance of the theme of cultural identity in the era of economic and culture globalization